The relationship between spiritual well-being and fear of cancer progression in Iranian cancer patients - Goudarzian, Amir Hossein; Mazhari, Seyed Amirhossein; Sobhanian, Pooria; Farhadi, Bahar; Kalantari, Soheyla; Taebi, Mozhgan (Frontiers in Psychology, 2025)
IntroductionThis study aimed to investigate the nuanced relationship between spiritual well-being and fear of cancer progression among individuals diagnosed with cancer.MethodsThe study was conducted in 2023 and utilized a predictive cross-sectional survey. A total of 398 cancer patients were recruited using convenience sampling. The Spiritual Well-Being Scale (SWBS) and the Fear of Progression (FOP) scale were used for data collection. Data analysis was performed using SPSS version 26, AMOS, and JASP to assess the reliability of the constructs and the potential relationship between the two main variables.ResultsThe mean age of the participants was 49.14 years (SD = 16.16, 95% CI: 47.55 50.74). All constructs demonstrated strong factorial validity and reliability. Simple linear regression analysis revealed that spiritual well-being significantly predicted fear of cancer progression (R2 = 0.064, F = 27, p < 0.001).DiscussionThe findings indicated a significant relationship between spiritual well-being and fear of cancer progression. These results highlighted the interconnectedness of spiritual well-being and fear of cancer progression among cancer patients.